A Systematic Review of Negative Work Behavior: Toward an Integrated Definition - Verschuren, Cokkie M.; Tims, Maria; de Lange, Annet H. (Frontiers in Psychology, 2021)
The objective of this systematic review was to identify the overlapping and unique aspects of the operationalizations of negative work behaviors (NWBs) to specify a new integrative definition of NWB. More specifically, we examined (1) how many operationalizations and conceptualizations of NWB can be identified, (2) whether these operationalizations can be categorized into facets, i. e., the nature of NWB, harm, actor types, and roles, with subcategories, (3) what the meaningful overlap in these operationalizations was, (4) whether the operationalizations tapped unique and meaningful elements, i.e., positive labels and dynamic processes, and (5) how the overlapping and unique elements of the operationalizations could be integrated into a new theory-based research model for NWB for future research. In the literature search based on the Prisma framework, Pubmed, PsycINFO, and Google Scholar, we identified k = 489 studies that met the inclusion criteria of our review. The results of these studies revealed 16 frequently studied NWB labels, e.g., bullying and aggression. Many of these could be categorized in the same way, namely, in terms of the type of behavior, type of harm, and type of actor involved in the NWB. In our new definition of NWB, we integrated the content of the overlapping and meaningful unique elements of the 16 labels.